Handball practice on bone health of female adolescents: evaluation of an eight-month competitive period - Tathyane Krahenbühl; Juliano Henrique Borges; Gil Guerra-Júnior; Antonio de Azevedo Barros Filho; Ezequiel Moreira Gonçalves (Revista Brasileira de Atividade Física e Saúde)
A strategy to prevent bone loss diseases (i.e., osteoporosis) would be to enhance the increase of bone mass during childhood and adolescence. The purpose of this study was to compare bone mineral density (BMD) and bone mineral content (BMC) between female adolescent handball players and peers who did not play (control group), and to assess the changes in BMD and BMC after eight-months of competitive period. Fifty-eight female adolescents (12–17 years old) were allocated into two groups: handball players (HG: n = 27) and control group (CG: n = 31). BMC and BMD were measured using dual-energy X-ray absorptiometry, and z-scores were calculated. Sexual maturity, menarche, peak height velocity (PHV), sun exposure and calcium intake were assessed. At baseline, the handball players showed greater BMC and BMD than control group (p < 0.05). These differences between groups disappeared after adjusting for weight, BMI, menarche and lean soft tissue. After competitive period, significant time-effects for BMC and BMD of total TBLH and lumbar spine (p < 0.01) were observed in the handball players. HG increased BMC and BMD of total body and lumbar spine after eight-month. The Z-score analysis showed significant group effects with greater BMD of total body, lumbar spine, femur and hip than control group.  The results showed that after eight-month competitive handball period, there was an increase in BMD of total body for handball players.